(untitled) (African Journal of Biomedical Research, 2020)
The aetiology of chronic leg ulcer in patients with sickle cell anaemia is multifactorial and complex, prevention and management is a daunting task. Micronutrients and antioxidants contribute to the pathogenesis of sickle cell disease and chronic leg ulcers. Therefore, this study was carried out to determine the serum levels of zinc, copper and vitamin E in sickle cell anaemia patients with chronic leg ulcer. Twelve sickle cell anaemia patients with leg ulcer (SLU), 12 sickle cell anaemia patients without leg ulcer (NLU) and 15 healthy volunteers who were age and sex-matched were recruited for the study. Questionnaires were administered to obtain biodata and history of ulcers with chronic leg ulcers. Venous blood was collected from all respondents and analyzed for complete blood count, zinc, copper and vitamin E levels. The data generated was analyzed using the Statistical Package for the Social Sciences (SPSS) version 23. Descriptive statistics such as frequency, counts, percentages, mean and standard deviation were used to summarize the result. Independent T test and ANOVA were used as appropriate determine significant association between variables. The level of significance was set at P value <0.05. The mean age of the sickle cell anaemia patients with chronic leg ulcer was 31± 10.3 years. There was no statistically significant association between the serum zinc, copper levels and the presence of chronic leg ulcer in sickle cell anemia patients. There was a statistically significant association between the serum vitamin E levels, and the presence of chronic leg ulcer in sickle cell anemia patients’ Low serum vitamin E level may play a significant role in the pathogenesis, sustenance and healing of sickle cell chronic leg ulcer. We therefore recommend the supplementation of vitamin E in the management of chronic leg ulcer in patients with sickle cell anaemia